Partisipasi Politik Masyarakat Dalam Perekrutan Calon Legislatif (Studi Kasus: Partai NasDem di Nagari Ujung Gading Kecamatan Lembah Melintang Kabupaten Pasaman Barat). - Sastika, Elma; Oktavia, Dian Anggaraini; Prahara, Surya (Pendidikan Sosiologi, 2014)
This study to describe the public participation in the process of recruiting candidates in Nagari Ujung Gading Kecamatan Lembah Melintang District Pasaman Barat. The theory used is social action theory proposed by Max Weber. This research is descriptive qualitative research subject is taken by purposive sampling criteria are the subject of this study group of the party and society. And data collection techniques used were observation, interview and documentation studies, data collection tool used is the researchers themselves who falls spaciousness, guide research and data, library books, camera and photograph. Data analysis technique used is data reduction, interpretation/data display, and verification/making conclusions.The results of this study are NasDem Party is a new political party standing but nevertheless NasDem party has its own way of recruiting members. Some requirement that must be met by candidates that have been defined by NasDem party. In addition, because NasDem a new political party that would desperately need the participation of the community.Â This participation is needed to support that partys NasDem better known among the general public. The form of participation NasDem party candidates are : First, the desire to run for legislative candidates. Second, following the admission process as candidates